Operando Identification of Liquid Intermediates in Lithium–Sulfur Batteries via Transmission UV–vis Spectroscopy. Issue 8 (21st April 2020) - He, Qi; Freiberg, Anna T. S.; Patel, Manu U. M.; Qian, Simon; Gasteiger, Hubert A.
Abstract : Lithium-sulfur (Li-S) batteries are facing various challenges with regards to performance and durability, and further improvements require a better understanding of the fundamental working mechanisms, including an identification of the reaction intermediates in an operating Li-S battery. In this study, we present an operando transmission UV–vis spectro-electrochemical cell design that employs a conventional sulfur/carbon composite electrode, propose a comprehensive peak assignment for polysulfides in DOL:DME-based electrolyte, and finally identify the liquid intermediates in the discharging process of an operating Li-S cell. Here, we propose for the first time a meta-stable polysulfide species (S3 2− ) that is present at substantial concentrations during the 2 nd discharge plateau in a Li-S battery. We identify the S3 2− species that are the reduction product of S4 2−, as deducted from the analysis of the obtained operando UV–vis spectra along with the transferred charge, and confirmed by rotating ring disk electrode measurements for the reduction of a solution with a nominal Li2 S4 stoichiometry. Furthermore, our operando results provide insight into the potential-dependent stability of different S-species and the rate-limiting (electro)chemical steps during discharging. Finally, we propose a viable reaction pathway of how S8 is electrochemically reduced to Li2 S2 /Li2 S based on our operando results as well as that reported in the literature.